2023
DOI: 10.1002/pen.26487
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted freeze‐drying strategy to enhance nanoparticle dispersion in aerogels: A case study on polyimide/silica nanocomposite aerogel

Hang Xiao,
Xi Zhao,
Jiangbo Lv
et al.

Abstract: Thermal protection materials should possess light weight, excellent thermal insulation, flame retardant and hydrophobic properties. Aerogel are considered a promising thermal protection material due to its high porosity and low density. Among them, nano‐silica/polyimide composite aerogel has been intensively studied as they can solve the problem of fragility of nano‐silica aerogel while ensuring thermal insulation and flame retardant performance. However, the problems of nanoparticle agglomeration and the tedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Significant differences in thermal insulation were demonstrated between the 5% and 3% solid content samples, with the 5% samples having higher thermal conductivity, indicating lower thermal insulation. This phenomenon can be explained by the higher porosity in samples with lower solid content, which increasing the air content within the material and results in lower density and lower thermal conductivity . Additionally, the thermal conductivity of PI aerogels varies with different molecular structures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant differences in thermal insulation were demonstrated between the 5% and 3% solid content samples, with the 5% samples having higher thermal conductivity, indicating lower thermal insulation. This phenomenon can be explained by the higher porosity in samples with lower solid content, which increasing the air content within the material and results in lower density and lower thermal conductivity . Additionally, the thermal conductivity of PI aerogels varies with different molecular structures.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon can be explained by the higher porosity in samples with lower solid content, which increasing the air content within the material and results in lower density and lower thermal conductivity. 28 Additionally, the thermal conductivity of PI aerogels varies with different molecular structures. SEM microstructural analysis showed that PI−II, which has lower thermal conductivity than PI−I, contains more pores and a complex network structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Additionally, treatment such as ultrasonic treatment has been employed to assist in dissolution and dispersion. 19 Further, various strategies including chemical and cationic crosslinking, coating with hydrophobic agents like silanes, reducing electrostatic repulsion through surface charge group protonation, and producing composite aerogel, have been applied to enhance the water resistant of cellulose aerogel. 7,15,[20][21][22] However, these supplementary gelation and modification procedures entail additional chemical inputs and energy consumption.…”
Section: Introductionmentioning
confidence: 99%